2021
DOI: 10.1111/ajo.13435
|View full text |Cite
|
Sign up to set email alerts
|

Using Google Trends to assess the Australian public's interest in topical gynaecology issues

Abstract: Our primary objective is to assess public awareness of topical issues in gynaecology by observing Google Trends information on internet searches in Australia and explore the linear relationship with landmark changes in policy or management. Following notable interventions such as new government policies, action plans and publications, there has been a 26.4% increase in searches for endometriosis, 3.9% increase in searches into transvaginal mesh, a 48.8% increase in searches for cervical screening and a 20.9% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…More than 400,000 Google searches on endometriosis are carried out per month in the United States alone [ 10 ]. An Australian study showed that a Google search for “endometriosis” increased by 26.4% after the announcement of the 2018 National Action Plan for Endometriosis in Australia [ 11 ]. Digital information seeking, including the use of eHealth websites, can contribute to improved health literacy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 400,000 Google searches on endometriosis are carried out per month in the United States alone [ 10 ]. An Australian study showed that a Google search for “endometriosis” increased by 26.4% after the announcement of the 2018 National Action Plan for Endometriosis in Australia [ 11 ]. Digital information seeking, including the use of eHealth websites, can contribute to improved health literacy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%